The myth of youth culture - Ramírez Varela, Francisco (Última Década, 2020)
When we began to address youth topics, we ended up describing this social group way beyond the range of ages and biologics, trying to accomodate them with a view to social sciences, which helps us explain the diverse phenomena which occur with youth, and in this way we understand their problems and social acts. Normally, these definitions touch the concept of «youth culture» where different youth manifestations are boxed in. We are now going to review the following pages, not only for value or relevance to the term «youth culture», but also to make a revision of some points of view on youth, and the association of the culture. This reflection brings us to the following questions, which we do not intend to answer, but rather reflect upon. Does «youth culture exist»?